2020
DOI: 10.1109/tns.2020.3004565
|View full text |Cite
|
Sign up to set email alerts
|

Selective Isotope CT Imaging Based on Nuclear Resonance Fluorescence Transmission Method

Abstract: The isotope selectivity of computed tomography (CT) imaging based on nuclear resonance fluorescence (NRF) transmission method using a quasi-monochromatic laser Compton scattering (LCS) gamma-ray beam in the MeV region was demonstrated at the Ultra Violet Synchrotron Orbital Radiation-III (UVSOR-III) Synchrotron Radiation Facility (Institute of Molecular Science, National Institute of Natural Science) for two enriched lead isotope rods (206 Pb and 208 Pb) implanted in an aluminum cylinder. Since these two rods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…We operated the laser system at a typical average power of 2.4 W during measurement of the gamma-CT images to generate an LCS gamma-ray beam with an intensity of 7 × 10 6 photons/s with 100% energy bandwidth at the full width at half maximum (FWHM) before collimation. The EGS5 Monte Carlo simulation code [19] was used to estimate the LCS gamma-ray beam's properties after the collimation [13]. The estimated flux of the LCS gamma-ray beam after collimation was 0.7 photons/s/eV at a maximum energy of 5528 MeV with 1.1% energy bandwidth at the FWHM.…”
Section: D Gamma-ct Image Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…We operated the laser system at a typical average power of 2.4 W during measurement of the gamma-CT images to generate an LCS gamma-ray beam with an intensity of 7 × 10 6 photons/s with 100% energy bandwidth at the full width at half maximum (FWHM) before collimation. The EGS5 Monte Carlo simulation code [19] was used to estimate the LCS gamma-ray beam's properties after the collimation [13]. The estimated flux of the LCS gamma-ray beam after collimation was 0.7 photons/s/eV at a maximum energy of 5528 MeV with 1.1% energy bandwidth at the FWHM.…”
Section: D Gamma-ct Image Measurementmentioning
confidence: 99%
“…The LCS gamma-ray beam flux passing through the collimator was numerically estimated using the EGS5 Monte Carlo simulation code [19], and thus we found that the flux density was 10 photons/s/eV and that the maximum energy was 5528 MeV with 2.9% energy bandwidth at the FWHM, which was able to excite the J π = 1 − NRF level at 5512 MeV in 208 Pb. Although the NRF-CT imaging technique is time-consuming, we were able to shorten the image acquisition time for each measurement point, which had been measured in our previous research [13] by adjusting the CT sample scanning pattern and increasing the LCS gamma-ray beam's intensity flux. The overall time needed to obtain a 3D NRF-CT image was approximately 48 h. Reference [14] gives more details on the experimental setup, the CT sample scanning plan, and a schematic diagram of the 3D NRF-CT image.…”
Section: D Nrf-ct Image Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the nuclear resonance fluorescence (NRF) in combination with computed tomography (CT) has been demonstrated as an isotope imaging technique, allowing for nondestructive inspection (NDI) for detecting hidden isotopic compositions of target materials that are of interest [1]. Furthermore, the isotope selectivity assessment [2] is a significant advancement in nuclear engineering. Physically, NRF is a nuclear process in which a nuclear state is excited through the absorption of a photon whose energy is nearly identical to the excited energy of the nuclear state.…”
Section: Introductionmentioning
confidence: 99%